Analysis of obstacles to English writing skills of electrical engineering students using interactive blog models - Munaiseche, Maya; Worotikan, Laela; Rooroh, Betsi; Pangemanan, Tjerie (Politeknik Negeri Bali, 2024)
This research aims to assess the students’ obstacles in writing skills using interactive blogs. The study employs both quantitative and qualitative descriptive methods. The focus of the study involved 100 students who answered a questionnaire consisting of 15 questions on Google Forms. The questions were categorized into three groups: indicators of interactive blog use, benefits, and their influence on learning in the digital era. The data from the questionnaire revealed that 58% of students had a fairly effective understanding of blogs, 76% found blogs useful, and 89% found blogs effective and practical. The students showed enthusiasm for writing prompts because blog entries can include text, images, audio, video, and hyperlinks, enriching the content and providing supporting information. However, some disadvantages mentioned included difficulties in using blogs, the influence of online networking (internet usage), lack of peer comments, and the time-consuming nature of maintaining blogs. Another challenge in writing is the use of grammar, particularly tenses. The integration of blogs affects meaningful learning experiences by preparing students for effective written communication in a fast-paced world and improving their writing techniques. Nonetheless, interactive blogs proved to be more effective in enhancing students' writing skills.